THE ROLE OF STATE AUTHORITIES IN THE IMPLEMENTATION AND ENFORCEMENT OF THE PRINCIPLE OF NON-DISCRIMINATION - Malicka, Agnieszka; Marta, Klimas (Anales Universitatis Apulensis Series Jurisprudentia, 2012)
The prohibition of discrimination in the Polish legal system is based on numerous international agreements and conventions, as well as on various internal regulations. Article 32.2 of the Polish Constitution constitutes a general prohibition of discrimination. Nevertheless, it is a very vague statement, which needs to be determined by specific non-discrimination principles. Primarily, such regulations can be found in labour law provisions. Moreover, since January 1, 2011, “The Act on the Implementation of Certain Provisions of the European Union in the Field of Equal Treatment” has been in force. This Act implements five European Union directives, which introduce non-discrimination principles in various aspects of social life. According to article 1 of the Equal Treatment Act, discrimination is prohibited on the basis of: sex, race, ethnicity, nationality, religion, belief, outlook on life, disability, age or sexual orientation. The Equal Treatment Act designates Ombudsman and The Government Plenipotentiary for Equal Treatment as those organs which are responsible for the implementation of government policy in the field of equal treatment. Even though the latter institution had already existed in Poland before the Act entered into force, its functioning and appointment are determined by this regulation. The existence of specific provisions aimed at counteracting discrimination does not prevent abuses. Both Ombudsman and The Government Plenipotentiary for Equal Treatment frequently intervene with state authorities responsible (especially with the respective Ministers) in cases which constitute an infringement of the principle of non-discrimination. These actions are undertaken to introduce amendments in existing legal regulations, thus adapting them to certain obligations derived from the principles of equal treatment and non-discrimination. Keywords: Convention to protect your rights and liberties, Council of Europe, equal treatment, EU-La, Implementation International Covenant on Civil and Political Rights, International Law.